2017
DOI: 10.1016/j.soard.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease and Barrett’s esophagus after laparoscopic sleeve gastrectomy: a possible, underestimated long-term complication

Abstract: In the present series the incidence of EE and of BE in SG patients was considerably higher than that reported in the current literature, and it was not related to GERD symptoms. Endoscopic surveillance after SG should be advocated irrespective of the presence of GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
156
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(181 citation statements)
references
References 31 publications
9
156
1
15
Order By: Relevance
“…Hernia Hiatal 11 (5,3%) 27-74% 33,37,38 Estenosis mesogástrica 3 (1,4%) 0,7-3,5% [11][12][13] Radiología (n = 93)…”
Section: Modificaciones Anatómicas Evaluadas Por Endoscopia Y Estudiounclassified
See 1 more Smart Citation
“…Hernia Hiatal 11 (5,3%) 27-74% 33,37,38 Estenosis mesogástrica 3 (1,4%) 0,7-3,5% [11][12][13] Radiología (n = 93)…”
Section: Modificaciones Anatómicas Evaluadas Por Endoscopia Y Estudiounclassified
“…Reflujo presente 42 (45,2%) 67% 11,33,38 Cardias dilatado 40 (43%) 60% 11,36,37,38 Hernia Hiatal 11 (11,8%) 60,8% 36,37,38 Estenosis mesogástrica 3 (3,2%)* 0,7-3,5 11-13 *bujía 34 French. con respecto a este punto están de acuerdo con las otras experiencias informadas (Tabla 3).…”
Section: Modificaciones Anatómicas Evaluadas Por Endoscopia Y Estudiounclassified
“…Data from the literature concerning the development of BE after LSG are scarce. Genco et al [3] showed a very high incidence of BE in LSG patients. Thus, endoscopic evaluation in the postoperative surveillance of LSG patients should be encouraged.…”
mentioning
confidence: 96%
“…Furthermore, the long-term issue of gastroesophageal reflux after sleeve has to be taken into account when discussing the safety of the 2 procedures. In a recent article by Genco et al, 6 17% of 110 asymptomatic patients showed signs of Barrett's esophagus after a mean of 58 months postsleeve. In other words, although the long-term side effects of the bypass procedures are well documented, as the first bypass procedures were performed over 50 years ago, we still do not know all possible side effects of sleeve gastrectomy yet.…”
mentioning
confidence: 98%
“…5 Till now, no validated score for late complications exists. However, the numbers mentioned by Fysekidis et al 6 for ''reoperations for major complications'' are incorrect. In the sleeve group, 2 patients had to be converted to bypass because of severe reflux, and another 2 were reoperated for insufficient weight loss as compared with 6 patients in the bypass group that were reoperated until 3 years postoperation (internal hernia, bowel obstruction, and insufficient weight loss).…”
mentioning
confidence: 99%